Efficacy and safety of robot-assisted deep brain stimulation for Parkinson’s disease: a meta-analysis - Huang, Zhilong; Meng, Lian; Bi, Xiongjie; Xie, Zhengde; Liang, Weiming; Huang, Jinyu (Frontiers in Aging Neuroscience, 2024)
Objective: This meta-analysis aims to assess the effectiveness and safety of robot-assisted deep brain stimulation (DBS) surgery for Parkinson's disease(PD).: Four databases(Medline, Embase, Web of Science and CENTRAL) were searched from establishment of database to 23 March 2024, for articles studying robot-assisted DBS in patients diagnosed with PD. Meta-analyses of vector error, complication rate, levodopa-equivalent daily dose(LEDD), Unified Parkinson's Disease Rating Scale(UPDRS), UPDRS II, UPDRS III, and UPDRS IV were performed.Results: A total of fifteen studies were included in this meta-analysis, comprising 732 patients with PD who received robot-assisted DBS. The pooled results revealed that the vector error was measured at 1.09mm (95% CI: 0.87 to 1.30) in patients with Parkinson's disease who received robot-assisted DBS. The complication rate was 0.12 (95% CI, 0.03 to 0.24). The reduction in LEDD was 422.31mg (95% CI: 68.69 to 775.94). The improvement in UPDRS, UPDRS III, and UPDRS IV was 27.36 (95% CI: 8.57 to 46.15), 14.09 (95% CI: 4.67 to 23.52), and 3.54 (95% CI: -2.35 to 9.43), respectively.Robot-assisted DBS is a reliable and safe approach for treating PD.Robot-assisted DBS provides enhanced accuracy in contrast to conventional frame-based stereotactic techniques. Nevertheless, further investigation is necessary to validate the advantages of robot-assisted DBS in terms of enhancing motor function and decreasing the need for antiparkinsonian medications, in comparison to traditional frame-based stereotactic techniques.